Pengaruh Pendidikan Karakter, Peran Keluarga, Dan Lingkungan Sosial-Digital Terhadap Kesiapan Sumber Daya Manusia Dalam Menghadapi Persaingan Global Di Era Society 5.0 (Studi pada Mahasiswa FEB UNISMA Angkatan 2022) - Putri Mauza Assyahidah; Khalikussabir Khalikussabir; Ahmad Subhan Mahardani (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to analyze the influence of character education, family role, and social-digital environment on human resource readiness in the Society 5.0 era. The research population consisted of individuals pursuing higher education, with a sample of 80 respondents obtained through purposive sampling. The dependent variable in this study was human resource readiness, while character education, family role, and social-digital environment were independent variables. The F test results show that the three independent variables together have a significant effect on human resource readiness. The partial t test results show that character education, family role, and social-digital environment each have a positive and significant effect, with the social-digital environment as the most dominant variable. The coefficient of determination (Adjusted R²) of 0.590 shows that 59% of the variation in human resource readiness can be explained by these three variables, while the remaining 41% is influenced by factors outside this study, indicating that there is still an opportunity for further research to explore additional factors that affect human resource readiness. Keywords: Character Education, Family Role, Social-Digital Environment, Human